Reticular Pseudodrusen and Its Importance in AMD - Prachi Abhishek Dave; Neha Bharti; Bhupesh Singh; Bhuvan Chanana; Sudhank Bharti (Delhi Journal of Ophthalmology)
This article aims to provide an insight into the pathophysiology and clinical features of the emerging entity called reticular pseudodrusen (RPD). The diagnosis of RPD requires multimodal imaging and it is important to distinguish them from other types of drusen. AMD can be a blinding disease with a huge impact of quality of life and the presence of RPD can further complicate the disease as RPD portend a faster progression of AMD to the wet form and are also known to be associated with geographic atrophy. Hence, it is important to diagnose this entity and these patients require a closer follow up.